Implementation of 3M Activities for Children's Fine Motor Development at Muslimat NU I Kindergarten, Pamekasan - Noer Cholis; Mediyana; Dewi Pusparini (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
This study aims to determine how the 3M activities (drawing, tearing, and sticking) can develop fine motor skills in early childhood at Muslimat NU I Kindergarten in Pamekasan. The method used was a descriptive qualitative approach, with the research subjects consisting of teachers and children in Group A (aged 4-5 years). Data were collected through observation, interviews, and documentation. The results showed that the 3M activities can improve hand-eye coordination, concentration, and creativity in children. This activity was implemented in three stages: planning, implementation, and evaluation, and has been proven to have a positive impact on children's fine motor development.